Implementation Model of The use of Prophylactic Antibiotics in Surgical Patients Hospital Type B - Ferry Ferdian Nugraha; Rina Mutiara; Arrozi Adhikara (Jurnal Health Sains, 2023)
Infectious diseases are still one of the important public health problems, especially in developing countries. The high incidence of Antibiotic resistance due to the irrational use of antibiotics is a special concern at this time. The government is also trying to control it through the Antimicrobial Resistance Control Program, including the rational administration of prophylactic antibiotics in surgery. Prophylactic antibiotics are antibiotics given before, during, and after surgical procedures to prevent complications of infection or infection of the surgical site (IDO). A retrospective and observational (non-experimental) study to know Patient characteristics, surgical characteristics, characteristics of the use of prophylactic antibiotics, rationality and cost analysis of using prophylactic antibiotics in Sectio Caesarea surgery and Appendectomy of patients at Hospital X Type B Jakarta in the period January 1 2021 – September 30 2021. The results of the study found that the selection of prophylactic antibiotics was not right (55.8%), the timing difference for prophylactic antibiotics was not right (84.5%), the prophylactic Antibiotic dose was not right (85.3%), all were correct the route of administration of prophylactic antibiotics by intravenous drip (100%), all of which are not appropriate for giving prophylactic Antibiotic intervals (100%) and entirely irrational in the use of prophylactic antibiotics in hospitals (100%). Hospitals can save costs, reduce the rate of Antibiotic resistance and reduce the incidence of surgical site infections by increasing physician compliance in using prophylactic antibiotics under hospital guidelines.